Advancing History Education in Higher Education: A Needs Analysis for Research-Based TPACK Models - Suarman Suarman; Isjoni Isjoni; Sumarno Sumarno; Asyrul Fikri (AL-ISHLAH: Jurnal Pendidikan, 2025)
The 21st Century demands innovative educational models that incorporate technological advances to support research and teaching. This study examines the need to develop a research-based history learning model using the Technological Pedagogical Content Knowledge (TPACK) framework (RBL-TPACK) to enhance history education. The research adopts a Research and Development (RD) approach, focusing on the analysis stage. Participants include 27 history lecturers and 107 students. Data collection involved observations, interviews, and questionnaires, with qualitative analysis used to assess the necessity of RBL-TPACK in history education. Findings indicate that research-based learning (RBL) is crucial for supporting lecturers' tridharma responsibilities and enriching local history education. However, the integration of RBL into lecture content and outputs remains suboptimal. Students demonstrated a strong preference for incorporating lecturers' research outputs into learning materials. The integration of digital tools via the TPACK framework offers a promising approach, enhancing theoretical and practical learning dynamics. The study highlights the potential of RBL-TPACK to foster historical thinking skills and enrich learning experiences. Despite its importance, gaps in integrating RBL and digital tools into teaching practices persist. Addressing these gaps through a structured RBL-TPACK model can better meet the demands of modern history education. Developing an effective and contextually relevant RBL-TPACK model is vital to advancing history education and addressing the challenges of 21st-century learning. This foundational analysis underscores the need for further development and implementation of this innovative approach.